Toward sportomics: Shifting from sport genomics to sport postgenomics and metabolomics specialties. Promises, challenges, and future perspectives - Bragazzi, N. L.; Khoramipour, K.; Chaouachi, A.; Chamari, K. (International Journal of Sports Physiology and Performance, 2020)
Together with experience, training, dietary intake, and other environmental factors, the biological and genetic makeup of an athlete play a major role in exercise physiology in terms of performance and outcomes.1 Sport genomics has shown that some DNA single-nucleotide polymorphisms can be associated with athlete level and performance (such as elite/world-class athletic status), having an impact on physical activity-related variables like endurance; strength; sprint; power; speed; flexibility; energetic expenditure; neuromuscular coordination; and respiratory, metabolic, and cardiorespiratory fitness, among others. Moreover, single-nucleotide polymorphisms have been shown to correlate with other parameters, including psychological traits.2 The athletic phenotype is extremely complex and multifactorial, depending on the combination of different features and characteristics.3 On this basis, sport performance is a "complex science," like that of metadata and multiomics profiles.